Answer :


By Transposition,


(x + 3)(2x 3) = (x + 2)( 3x – 7)


2x2 + 6x – 3x – 9 = 3x2 + 6x – 7x -14


2x2 + 3x – 9 = 3x2 – x -14


3x2 – 2x2 – x – 3x – 14 + 9 = 0


x2 – 4x – 5 = 0


x2 – 5x + x – 5 = 0


x(x 5) + 1(x 5) = 0


(x + 1)(x 5) = 0


This gives 2 equations,


i. x + 1 = 0


x = -1


ii. x – 5 = 0


x = 5


Hence, x = -1 or x = 5


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses